The Role of Cardiovascular Magnetic Resonance in Congenital Heart Disease - Puranik, Rajesh; Muthurangu, Vivek; Taylor, Andrew M (SA Heart Journal, 2017)
The increasing prevalence of congenital heart disease (CHD) can be attributed to major improvements in diagnosis and treatment. Although echocardiography is the most commonly used imaging modality for diagnosis and follow up of subjects with CHD, the evolution of both cardiovascular magnetic resonance (MR) imaging and computed tomography (CT) does offer new ways to visualize the heart and the great vessels. The development of cardiovascular MR techniques such as spinecho and gradient-echo imaging, velocity-encoded phase contrast MR and gadolinium-enhanced MR angiography allow comprehensive assessment of cardiac anatomy and function. This provides information about the long-term sequelae of the underlying complex anatomy, hemodynamic assessment of residual post-operative lesions and complications of surgery. As much of the functional data in CHD patients is usually acquired with invasive X-ray angiography, non-invasive alternatives such as cardiovascular MR and CT are desirable. This review evaluates the role of both these modalities in the management of subjects with CHD, particularly detailing recent developments in imaging techniques as they relate to the various CHD diagnoses we commonly encounter in our practice.